PanicRoom: a virtual reality-based Pavlovian fear conditioning paradigm - Lucifora, Chiara; Gangemi, Aldo; D’Italia, Giovanni; Culicetto, Laura; Ferraioli, Francesca; Grasso, Giorgio Mario; Vicario, Carmelo Mario (Frontiers in Psychology, 2024)
Introduction Pavlovian fear conditioning is an experimental paradigm used to study the acquisition and extinction of fear responses and the various aspects of fear and anxiety. We developed a virtual reality (VR) version of this paradigm to leverage the benefits of virtual reality, such as ecological validity, standardization, safety, and therapeutic applications. Our objective was to create an open-source and immersive environment for studying fear-related responses using Unity Engine 3D and the Oculus Rift device. Methods In this virtual environment, the participants encountered a monster screaming at 100 dB approaching them as the fear-inducing stimulus (unconditioned stimulus or US). Our protocol included three sessions: habituation, acquisition, and extinction, with two stimuli associated with different doors (blue vs. red). The blue door (CS+) was linked to the US, while the red door (CS−) was the control. We tested this VR paradigm on 84 young participants, recording their skin conductance response (SCRs) and fear stimulus ratings (FSRs) on a 10-point Likert scale. Results The findings showed significantly higher SCRs and FSRs for CS+ as compared to CS− during the acquisition phase and higher SCRs and FSRs for CS+ during the acquisition phase as compared to the habituation and extinction sessions. Discussion and conclusions These results supported the reliability of the protocol for studying fear and anxiety-related conditions.